2017
DOI: 10.1007/s11596-017-1728-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RNA interference combined with ultrasonic irradiation and SonoVue microbubbles on expression of STAT3 gene in keratinocytes of psoriatic lesions

Abstract: The most effective sequence of small interfering RNA (siRNA) silencing STAT3 of psoriatic keratinocytes (KCs) was screened out, and the effects of the most effective siRNA combined with ultrasonic irradiation and SonoVue microbubbles on the expression of STAT3 of KCs and the dose- and time-response were investigated. Three chemically-synthetic siRNAs targeting STAT3 carried by Lipofectamine 3000 were transfected into KCs, and the effects on STAT3 expression were detected, then the most effective siRNA was sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…[ 5 ] Our previous studies had shown STAT3 siRNA carried by Lipofectamine 3000 combined with ultrasonic irradiation and SonoVue microbubbles could effectively knock down and downregulate the protein expression of STAT3 gene in psoriatic KCs. [ 7 ] Subsequently, we applied this kind of experimental method to investigate the effects about STAT3 gene silencing on the proliferation and apoptosis of psoriatic KCs and the relative mechanisms. The same study was not found in previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] Our previous studies had shown STAT3 siRNA carried by Lipofectamine 3000 combined with ultrasonic irradiation and SonoVue microbubbles could effectively knock down and downregulate the protein expression of STAT3 gene in psoriatic KCs. [ 7 ] Subsequently, we applied this kind of experimental method to investigate the effects about STAT3 gene silencing on the proliferation and apoptosis of psoriatic KCs and the relative mechanisms. The same study was not found in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 6 ] Our previous studies had screened out the most effective sequence of siRNA targeted to the STAT3 gene of psoriatic KCs and also showed the optimal dose- and time-response of the siRNA combined with ultrasonic irradiation and SonoVue microbubbles on knocking down the STAT3 expression of psoriatic KCs. [ 7 ] In this study, the effects of STAT3 siRNA combined with ultrasonic irradiation and SonoVue microbubbles on the proliferation and apoptosis of psoriatic KCs were investigated, and the relative mechanisms were discussed. This study aimed to provide a new way of exploring gene therapy in the treatment of psoriasis.…”
Section: Introductionmentioning
confidence: 99%